Nearly Zero Energy Building Refurbishment 2013
DOI: 10.1007/978-1-4471-5523-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Nanogel Windows

Abstract: This chapter deals with the application of highly energy-efficient windows and skylights with silica nanogel as a strategy in the building refurbishment. Aerogel windows seem to have the largest potential for improving the thermal performance and daylight in fenestration industry, because of very low conductivity, density, and a good optical transparency. A state-of-the-art review of nanogel windows in building applications is firstly presented. Then, the proprieties of nanogel glazings in terms of thermal, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Silica aerogel can be manufactured by supercritical drying of colloidal silica gel under high temperature and pressure [71][72][73][74]. The material comprises ~1-nm-diameter silica particles that are interconnected and form a sparsely packed structure with pore sizes of 1 to 100 nm.…”
Section: Solid Materialsmentioning
confidence: 99%
“…Silica aerogel can be manufactured by supercritical drying of colloidal silica gel under high temperature and pressure [71][72][73][74]. The material comprises ~1-nm-diameter silica particles that are interconnected and form a sparsely packed structure with pore sizes of 1 to 100 nm.…”
Section: Solid Materialsmentioning
confidence: 99%
“…The former has a higher light transmittance and lower U-values. Buratti and Moretti [76,77] compared the performance of seven different glazings and found that granular aerogel glazing was the most efficient system especially for cold climates leading to an annual energy demand decrease of about 10-20% when compared to the standard glazings. The advantages in using aerogel glazing have been recently confirmed by other authors [78,79].…”
Section: Nanotechnology Opportunities For Energy Efficient Built Environmentmentioning
confidence: 99%
“…Aerogel based windows constitute very promising high tech alternatives. Buratti and Moretti (2013) compared the performance of seven different glazings and found that granular aerogel glazing was the most efficient systems especially for cold climates leading to an annual energy demand decreases of about 10-20% when compared to the standard glazings. However, the eco-efficiency of aerogel windows still remains to be proven by life cycle assessment investigations.…”
Section: Nanotechnology Opportunities For Eco-efficient Built Environmentioning
confidence: 99%